Profil Kesalahan Siswa dalam Menyelesaikan Soal Cerita Matematika SMP Ditinjau Dari Kemampuan Berpikir Kritis - Restie Amelia; Lukman El Hakim; Anny Sovia; Ellis Salsabila; Tian Abdul Aziz; Flavia Aurelia Hidajat (Program Studi Pendidikan Matematika, 2025)
This study was motivated by the low level of critical thinking skills among junior high school students in solving mathematical word probleims, as evident from previous studies and the researcher's initial observations in the field. This study aims to describe the profil of junior high school students' errors in solving mathematical story problems in terms of critical thinking skills. The method used is qualitative descriptive with 32 seventh-grade students as subjects at a public junior high school in South Tambun in the 2024/2025 academic year. The research instrument was an essay test containing five story problems developed based on critical thinking ability indicators, including providing simple explanations, providing further explanations, determining strategies and techniquies, and drawing conclusions. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results showed that most students were in the low critical thinking ability category (63%) and the rest were in the moderate category (37%), while no students reached the high category. Students with low critical thinking abilities tended to make mistakes in almost all indicators, while students with moderate abilities were able to meet most of the indicators but were not consistent, especially in determining solution strategieis and drawing conclusions. These findings indicate that the main weakness of students lies in the aspects of strategy planning and drawing conclusions, so mathematics learning that emphasizes the development of critical thinking skills through non- routine story problems and the use of targeted assessment rubrics is needed.